Faculty Development for Teaching International Students: A Seminar Series Approach - Burke, Zoe; Haan, Jennifer; Gallagher, Colleen (Journal of International Students, 2020)
This paper describes and reflects on a seminar series in linguistically responsive instruction across academic disciplines, providing faculty in different institutions a model for faculty development in working with international students.